A SISTEMATIZAÇÃO DO RETALHO DO MÚSCULO LATÍSSIMO DO DORSO EM DECÚBITO DORSAL - Andrade, Fernando Antônio Gomes de; Duarte, Fernando Gaia; Chaves, Luciano Ornelas; Bezerra, Ricardo Nogueira; Salvador Filho, Luís Henrique Alves; Silva, Simone Vicente Dias da (Gep News, 2017)
Tipo de Apresentação: Comunicação Oral.